Identificação,síntese e caracterização de um epitopo descontínuo TsNTxP: uma anatoxina natural do veneno do escorpião Tityus serrulatus - Clara Guerra Duarte (2007)
Envenoming by the scorpion Tityus serrulatus is a major health problemin Brazil, especially in the state of Minas Gerais. TsNTxP is a non-toxic and immunogenic protein from the venom of scorpion Tityus serrulatus witch has the property to elicit neutralizing antibodies against the whole venom. The SPOT method of multiple peptide synthesis was used to prepare, on cellulose membranes, a hundred and fifty three overlapping octadecapeptides covering the complete amino acid sequence of TsNTxP in order to map possible conformational epitopes. Anti-TsNTxP neutralizing rabbit antibodies revealed that GREGYPADGGGLPDSVKI is one immunodominant diepitope. This epitope contains two antigenic regions of the TsNTxP, one in the N-terminal part (residues 18 (GREGYPAD)) and the other in the C-terminal part (residues 4754(GLPDSVKI)). After synthesis and purification, antibodies were raised in BALB/c mice against the diepitope conjugated to ovalbumin (OVA) withglutaraldehyde. In vivo protection assays one week after the last immunization showed that immunized mice could resist the challenge of three-fold the LD50 of the T. serrulatus whole venom, a dose that killed all control non-immune mice. The mice immunized with this preparation developed an antibody response that persisted nine weeks after the end of the immunization protocol. Rabbit immunization with the same immunogen produced specific antibodies that werent very efficient in neutralizing the lethal effects of the venom, although they were capable of retarding the envenoming symptoms and the time of death.